Assessing circularity of multi-sectoral systems under the Water-Energy-Food-Ecosystems (WEFE) nexus. (1st August 2022) - Nika, C.E.; Vasilaki, V.; Renfrew, D.; Danishvar, M.; Echchelh, A.; Katsou, E.
Highlights: Expanded-MSWCA for systematic circular economy indicators selection. 67 circularity indicators related to 13 sustainable development goals. The retrofit system outcompetes the baseline in terms of circularity performance. Circularity performance optimization of retrofit system by 8–61%. The optimized system mitigates lurking circularity risks of uncontrollable events. Abstract: The Multi-Sectoral Water Circularity Assessment (MSWCA) is a methodological framework developed for circularity assessment of the Water-Energy-Food-Ecosystems nexus. It involves five methodological steps and includes an indicators list for the selection of case-specific indicators. This study expands the MSWCA to provide a systematic approach for selecting indicators, considering system's circular actions and multi-functionality, the capture of implemented changes, the three CE principles and the sustainable development goals. Furthermore, this study differentiates between benchmark and dynamic circularity assessment and applies the expanded MSWCA in a water system of the HYDROUSA H2020 project. The benchmark assessment indicates that the HYDROUSA system achieves a 75% increase of water circularity, 76–80% increase of nutrients circularity and 14% reduction of operational `carbon footprint compared to the baseline scenario. The dynamic assessment highlights that additional measures can improve the system's circularity performance (e.g. water circularity can reach 94%) and mitigate risks occurring from uncontrollable changes. Graphical abstract: Image, graphical abstract